Accounting and Cost Analysis for the Functional Sphere of the Business - M. A. Vakhrushina; A. U. Panakhov (Учёт. Анализ. Аудит, 2023)
Today, there is a high demand to analyze the costs of organizations associated with and divided by enlarged functional areas such as management automation, personnel management, training, recruitment (hiring), environment and ecology, logistics, innovation, compliance, and many others. At the same time, the set of practices related to the preparation and use of functionally identified cost data is currently characterized by the problem of fragmentation and lack of consistency: the practices are mainly focused on individual management needs associated with a single functional area and are not universal. It seems important to synchronise the approaches applied to cost analysis in different functional areas and to propose a universal toolkit to systematise the existing practices of such analysis within a single area of investigation. In this regard, the subject of the study is the set of tools for structural cost analysis by functional areas. The objective of the study is to disclose and to substantiate the functional area as an applied object of cost accounting and analysis and to propose applied tools for providing functional cost area analysis synchronised with the modern management needs, as well as to develop universal approaches to their structural analysis based on the needs of modern management. As a result of the study, a systematized vision of information-analytical support for functional area management is proposed and systematised. A scheme is shown for using information on the functional area costs in the context of its components in various dimensions and levels of management. A universal structure of the analytical cost cube is proposed. A consolidated functional area cost report is proposed, with providing the detail rules how to calculate its structural indicators; the universal structure of the consolidated register of the costs grouped on functional spheres in several applied dimensions is developed; the structure of the consolidated report on costs of functional sphere with detailing of rules of calculation of included in it is presented. A system of coefficients is proposed, including the coefficient of the function burden on the enterprise economy, coefficients of the internalization (vertical integration), centralization and rootedness of the functional sphere.